Performance Evaluation of a Cotton Heaping Machine - Shukla, S K; Arude, V G; Nath, Jyoti M; Patil, P G (Journal of Agricultural Engineering, 2010)
A cotton loading/unloading machine for heaping operation was developed and evaluated for its capacity and fibre parameters. A centrifugal fan with open impeller was modified as Rembert fan by attaching a conical disc over the fan impeller. The major components of the machine were inlet flexible pipe, casing, impeller, perforated conical disc, electric motor, outlet GI pipe and trolley. Three conical discs of different perforation sizes were tested to optimize the output and efficiency of the developed machine. A conical disc with 3 mm perforation size was found as optimum size, without choking, for attachment at the inlet side of impeller. The capacity of the developed machine for heaping was 2400 kg cotton/h. The average fine trash content removal efficiency was 20.8 percent. No measurable fibre damage was observed during conveying of cotton.